2021
DOI: 10.1001/jamanetworkopen.2021.18141
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Long-term Outcomes of Valve-Sparing and Transannular Patch Procedures for Correction of Tetralogy of Fallot

Abstract: IMPORTANCEThe choice of the right surgical technique for correction of tetralogy of Fallot (TOF) is contentious for patients with a moderate to severe right outflow tract obstruction. The use of a transannular patch (TAP) exposes patients to chronic pulmonary regurgitation, while valve-sparing (VS) procedures may incompletely relieve pulmonary obstruction.OBJECTIVE To compare 30-year outcomes of TOF repair after a VS procedure vs TAP. DESIGN, SETTING, AND PARTICIPANTSThis retrospective population-based cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 46 publications
0
13
1
Order By: Relevance
“…[15][16][17] There has been a growing enthusiasm for TOF repair techniques implying preservation of the pulmonary valve and its annulus, thus prolonging time until PVR. 12 Historical series confirm that late PVR is significantly less common whenever the annulus remained intact. However, whether all forms of valve preservation translate into late clinical advantages is difficult to prove.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…[15][16][17] There has been a growing enthusiasm for TOF repair techniques implying preservation of the pulmonary valve and its annulus, thus prolonging time until PVR. 12 Historical series confirm that late PVR is significantly less common whenever the annulus remained intact. However, whether all forms of valve preservation translate into late clinical advantages is difficult to prove.…”
Section: Discussionmentioning
confidence: 98%
“…Since the first successful TOF-repair by Lillehei and colleagues in the 1950s, outcomes have significantly improved, with excellent long-term survival and low risks for late sudden death. 12 13 14 However, long-term studies after TOF-repair have all shown frequent need for PVR due to progressive pulmonary valve regurgitation, right ventricular dysfunction, and decreased functional capacity. 15 16 17 There has been a growing enthusiasm for TOF repair techniques implying preservation of the pulmonary valve and its annulus, thus prolonging time until PVR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 68 Current surgical practices with more valve‐sparing operations and fewer transannular patches for ToF are likely already influencing the context in which EDFF is observed, so research into the implications of EDFF may differ from the historical baselines established in this analysis. 69 …”
Section: Discussionmentioning
confidence: 99%
“…However, the predicted disadvantage of this procedure, the postoperative pulmonary regurgitation (PR), was affirmed in a significant number of patients who suffered pulmonary insufficiency (PI), heart failure, arrhythmia, and even sudden cardiac death ( 13 , 14 ). Preserving or reconstructing pulmonary valve function is the best way to prevent PR and reduce the risk of adverse cardiovascular events ( 15 ). All procedures, including commissurotomy, PCA, pulmonary valve reconstruction, and IBPV can be performed to maintain pulmonary valve function to some extent.…”
Section: Introductionmentioning
confidence: 99%